Highly viscoelastic films at the water/air interface: α-Cyclodextrin with anionic surfactants - Luviano, Alberto S; Hernández-Pascacio, Jorge; Ondo, Daniel; Campbell, Richard A; Piñeiro, Ángel; Campos-Terán, José; Costas, Miguel (Journal of colloid and interface science, 2020)
This work showcases the remarkable viscoelasticity of films consisting of α-cyclodextrin (α-CD) and anionic surfactants (S) at the water/air interface, the magnitude of which has not been observed in similar systems. The anionic surfactants employed are sodium salts of a homologous series of n-alkylsulfates (n = 8-14) and of dodecylsulfonate. Our hypothesis was that the very high viscoelasticity can be systematically related to the bulk and interfacial properties of the system. Through resolution of the bulk distribution of species using isothermal titration calorimetry, the high dilatational modulus is related to (α-CD)2:S1 inclusion complexes in the bulk with respect to both the bulk composition and temperature. Direct interfacial characterization of α-CD and sodium dodecylsulfate films at 283.15 K using ellipsometry and neutron reflectometry reveals that the most viscoelastic films consist of a highly ordered monolayer of 2:1 complexes with a minimum amount of any other component. The orientation of the complexes in the films and their driving force for adsorption are discussed in the context of results from molecular dynamics simulations. These findings open up clear potential for the design of new functional materials or molecular sensors based on films with specific mechanical, electrical, thermal, chemical, optical or even magnetic properties.
Keywords: Ellipsometry; Isothermal titration calorimetry; Water/air interface; α-Cyclodextrin; Dilatational modulus; Neutron reflectometry; Surfactant; Viscoelastic films